Structuring the situation: Organizational goals trigger and direct decision-making - Greve, Henrich R. (Frontiers in Psychology, 2023)
Organizational goals are assigned to individuals, and thus differ from goals that individuals voluntarily adopt. The Carnegie School has a significant research stream on how organizations are affected by goals, with a focus on how disappointing performance disrupts regular organizational behavior and triggers a search for alternative actions. We have a good understanding of the organization-level process of setting aspiration levels, triggering search for alternatives, and making decisions, but the individual-level mechanisms contributing to it are less well known. An assessment of the progress of Carnegie School research so far reveals a list of research questions that should be resolved in order to understand how individual updating of aspiration levels, triggering of search, directing of search, and decision-making help explain organizational responses to goals. The role of construal, or interpretation, in guiding these processes is a central theoretical mechanism that needs further investigation.